Jhwo Bhoye: Embodying Newar Indigenous Knowledge for Cultural and Ecological Sustainability in Bhaktapur - Phelu, Rajan (NPRC Journal of Multidisciplinary Research, 2025)
This study aims to explore Jhwo Bhoye [a Newari communal feast in Bhaktapur] as an essential manifestation of Indigenous Knowledge Systems (IKS), highlighting its function in maintaining ecological practices and cultural identity. IKS refers to the traditional knowledge, practices, and beliefs developed by indigenous communities over generations, often deeply connected to their environment, culture, and spirituality. Jhwo Bhoye incorporates local ingredients, typical cooking methods, and rituals that embody the Newari perspective of being intertwined with the natural world and society. By employing an ethnographic approach that includes semi-structured interviews and participant observation carried out in 2024, this study examines how Jhwo Bhoye exemplifies IKS principles addressing the question: How does it maintain ecological and cultural practices in Bhaktapur? The findings suggest that Jhwo Bhoye uses sustainable methods to reduce waste, such as employing seasonal ingredients and biodegradable materials, which are aligned with agro-ecological cycles. Honoring ancestors and deities, and strengthening spiritual and social links, the sequential service of foods in Jhwo Bhoye reflects cultural symbolism and nutritional balance. Urbanization and modern trends like buffet-style dining, however, pose a threat to its survival, especially among younger generations who are attracted to modern lifestyle. The paper argues that by preserving Newari identity and ecological wisdom, Jhwo Bhoye serves as a decolonial praxis that opposes globalized cultural homogenization. Its methods, which prioritize community-driven resource management, provide insightful perspectives for sustainable development. Incorporating IKS into educational and policy frameworks is crucial to halting the loss of this intangible heritage. In order to preserve cultural and ecological resilience in the face of globalization, this research advocates for the inclusion of Jhwo Bhoye in modern curriculum that contributes to the wider discourse on conserving indigenous knowledge.